(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Pearl millets (Pennisetum glaucum) are important but underutilized crops found in tropical and semi-arid regions of the world, including Northern Nigeria. A survey report of women in Kaduna, Northern Nigeria, revealed that milk obtained from grains of Pearl millet have been utilized to enhance lactation, even in cases of adoptive nursing. Objectives: The aim of this study is to prepare aqueous slurry of Pearl millet grains, freeze-dry into powders, characterize and then evaluate the powders for galactogogue activity in female Wistar rats, in comparison to domperidone, a dopamine antagonist used as a lactogenic agent. Methods: The aqueous slurry of millets was freeze-dried and characterized for morphology, crystallinity (Fourier Transform Infra-red spectroscopy, FTIR and X-ray diffraction analysis, XRD), viscosity, flow and compaction properties. Animal studies were carried out to evaluate the galactogogue effect and histopathological examination was done on the 15th day of parturition. Toxicological testing to determine the LD50 was performed using Lorke’s method. Results: The morphology, FTIR and XRD spectra confirmed the disruption of the granules when freeze-dried. Freeze-drying improved flow and showed good compactibility, indicating potential for formulating the powders into tablets. Weight gain and histopathological examination revealed improved milk secretion and milk emptying in rats. The LD50 showed that the highest dose of 6000µg/kg gave no mortality. Conclusion: The freeze-dried powders of Pearl millet slurry were free flowing, capable of compaction and produced increased secretion and emptying of milk in Wistar rats, showing potential as a galactogogue for use in humans and the dairy industry.